Guanxi and its influence on the judgements of Chinese auditors - Scully, Glennda; Woodbine, Gordon; Fan, Ying Han (Routledge, 2012)
A major objective of this study is to develop a guanxi scale with two dimensions, favour-seeking guanxi and, for the first time, a rent-seeking guanxi, based on Ang and Leong’s (2000) guanxi scale and Su and Littlefield’s (2001) classifications of guanxi orientations. The relationship between Chinese auditors’ guanxi orientations and their ethical judgments is also reported. A survey methodology was used in this study and519 useable respondents were included. Results of this study show these two guanxi dimensions are relatively independent. It was also found that Chinese auditors’ favour seeking guanxi orientations were positively associated with their ethical judgments but their rent-seeking guanxi orientations negatively impacted on their ethical judgments.